Unmasking the silent threat: ST-elevation myocardial infarction in 37-year-old woman - Aflakha, Zakiyyatul; Bakhriansyah, Jordan; Yomara, Romadhana Trisnha; Firdaus, Much. Muzakky Misbachul; Alsagaff, Mochamad Yusuf (Universitas Brawijaya, 2026)
Background: ST-elevation myocardial infarction (STEMI) has been traditionally associated with elderly males; however, its prevalence is on the rise among young women. Women often manifest with non-atherosclerotic causes of ischemic heart disease, including plaque erosion and spontaneous coronary artery dissection (SCAD); while atypical symptoms and other pathophysiological processes often result in delay in diagnosis and diagnostic or treatment differences. This case underscores the crucial role of early recognition of atypical symptoms, careful assessment of risk factors, and thoughtful selection of the best management strategies. Case Presentations: A 37-year-old woman with inadequately controlled hypertension, who did not have any traditional risk factors, presented to the emergency department with diaphoresis and epigastric pain. Initial electrocardiogram (ECG) showed inferoposterior STEMI, and coronary angiography revealed total mid RCA occlusion with nonsignificant LAD stenosis. She was immediately taken to the cath lab and primary PCI was performed with direct stenting to improve myocardial perfusion. After PCI, the patient experienced uneventful TIMI III flow restoration and was discharged on DAPT and optimal medical therapy. She was asymptomatic at the one-year follow-up, which underscores the efficacy of direct stenting in specific STEMI. Conclusions: Young women with STEMI represent a distinct and under-recognized group requiring sex specific risk stratification and tailored management to improve outcomes. Further research is needed to identify optimal therapeutic strategies for this population.